KLASIFIKASI KUALITAS MUTU JAGUNG DENGAN MENGGUNAKAN METODE DECISION TREE PADA DINAS PERTANIAN BOJONEGORO - Moch. Lutfi (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
Corn is a food source in several regions in Indonesia, in addition to being a human food source, corn can also be used as animal feed ingredients. Quality classification of corn is needed to produce quality products. The quality of corn quality is determined by the attributes of varietas, lengths, shapes, colors, flavors, techniques, seasons, pests, PH and the quality used as a classification process of quality using a decision tree algorithm. The results of the study were compared with three decision tree criteria namely gain ratio, information gain and Gini index. Accuracy results show that the highest criterion value is 72.76% in the Gini index criterion and the lowest value is the criterion gain ratio of 60.67%.